PENGARUH PERCEIVED PERISHABILITY, PERCEIVED LOW PRICE DAN FINANCIAL LITERACY TERHADAP IMPULSIVE BUYING BEHAVIOR - Tifanisyaffa, Azelika; Firmialy, Sita Deliyana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
One of the e-commerce In Indonesia was chosen as the focus of this study as it is able to represent a significant growing consumer trend, especially in the evolution of online shopping with the implementation of their regularly scheduled sales promotion, the Tanggal Kembar Event. Perceived perishability, perceived low price, and financial literacy are expected to influence customers emotions through attitude towards sales promotion event onto impulsive buying behavior, whether it is positively or negatively with time limitation, price reduction, and finance literacy driven by any form of promotion given by the e-commerce as a stimulus. The research technique used in this study is a quantitative approach with a verificative method where the data results are obtained from distributing questionnaire to 115 Gen Z respondents who use the e-commerce in West Java. SmartPLS was used for data testing. The study findings indicate that perceived perishability and perceived low price has a significant effect on attitude towards sales promotion event, and on impulsive buying behavior. Attitude towards sales promotion event has a significant effect on impulsive buying behavior. Financial literacy negatively affects impulsive buying behavior and attitude towards sales promotion events, which also failed to intervene in the relationship of financial literacy with impulsive buying behavior. We suggest that in the future, researchers should use variables regarding financial decision-making such as financial inclusion to demonstrate more on the effect towards attitude and impulsive buying behavior. The chosen e-commerce are encouraged to continuously refine their Tanggal Kembar sales promotion event program. Considering perceived perishability and perceived low price may become a major opportunity for the e-commerce in triggering an attitude towards sales promotion event that can stimulate customers' impulsive buying behavior.